Solve for c 6-(4c+2)=9

Math
6-(4c+2)=9
Simplify 6-(4c+2).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
6-(4c)-1⋅2=9
Multiply 4 by -1.
6-4c-1⋅2=9
Multiply -1 by 2.
6-4c-2=9
6-4c-2=9
Subtract 2 from 6.
-4c+4=9
-4c+4=9
Move all terms not containing c to the right side of the equation.
Tap for more steps…
Subtract 4 from both sides of the equation.
-4c=9-4
Subtract 4 from 9.
-4c=5
-4c=5
Divide each term by -4 and simplify.
Tap for more steps…
Divide each term in -4c=5 by -4.
-4c-4=5-4
Cancel the common factor of -4.
Tap for more steps…
Cancel the common factor.
-4c-4=5-4
Divide c by 1.
c=5-4
c=5-4
Move the negative in front of the fraction.
c=-54
c=-54
The result can be shown in multiple forms.
Exact Form:
c=-54
Decimal Form:
c=-1.25
Mixed Number Form:
c=-114
Solve for c 6-(4c+2)=9

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top